FACTORS THAT AFFECT THE QUALITIES OF ENVIRONMENTAL JOURNALISTS - Şule Öztürk (Erciyes University, 2011)
Primary agenda of developing countries has become an economic development.Environmental issues in these countries usually are approached in an economical framing andnews about environment is relating an environmental investment of corporations. Environmentalissues are not involved in media except life contingency. Turkey‘s environmental problems arein a non-return path because of industrialization, irregular urbanization and the improving energyneeds. Attention to these problems and creating a public opinion about environmental issues ismedia's role.Advertisers, agencies, media organizations, news routines, editorial process and qualities ofjournalists affect to take in place environmental news in media. All this factors are known asnews production process. Subject of this study is how journalists can influence the dynamic ofnews production process. The aim of this study is to make a profile about environment journalist.This research's data will collect the method of in-depth interview with journalists who work asan environment reporter. Collected data will be analyzed in ideological dimension of currentagenda that generated by journalism, nature, news routines, organizational structure andadvertisers, companies, politicians and NGO's and government.